CRITICAL MAKING: AMISH INNOVATION FOR COMMUNITY EMPOWERMENT - Ems, Lindsay (AoIR Selected Papers of Internet Research, 2015)
This paper identifies one communication strategy used by the Amish to protect their cultural autonomy in the digital age. Based on recent ethnographic fieldwork in two Indiana Amish settlements and artifact analyses of devices appearing in advertisements in a popular Amish trade journal, this paper explores the political implications of everyday socio-technical making practices. In particular, this paper explores everyday socio-technical innovations, including professional artifacts and arrangements, which reflect and protect Amish religious and cultural values in an increasingly digital economy. The innovations presented in this paper are positioned as mundane and everyday decisions and professional practices that have profound political implications for the empowerment of Amish communities to resist the assimilation of their culture in mainstream society in an increasingly globally networked world.